Needle trap sampling thermal-desorption resonance enhanced multiphoton ionization time-of-flight mass spectrometry for analysis of marine diesel engine exhaust1. Issue 8 (21st April 2015) - Kleeblatt, Juliane; Stengel, Benjamin; Radischat, Christian; Passig, Johannes; Streibel, Thorsten; Sippula, Olli; Rabe, Rom; Harndorf, Horst; Zimmermann, Ralf
<x xml:space="preserve">Abstract</x> The manuscript demonstrates the successful application of NTD-TD-REMPI-TOFMS for analysis of volatile organic compounds (VOC) in ship diesel engine exhaust.